SLIP RATE VALUE INVESTIGATION FOR FAULTS IN INDONESIA BASED ON EARTH-QUAKE SCALING RELATIONSHIP - Jannah, Miftahul
Indonesia's tectonic setting makes the country highly susceptible to earthquakes. According to data released by the USGS, there have been at least 5,072 earthquakes between 2020 and 2022. Earthquake disasters in Indonesia are categorized as events causing significant losses. Given this situation, mitigation efforts are crucial. One mitigation measure that can be undertaken is modeling earthquake fault sources using the Probabilistic Seismic Hazard Assessment (PSHA) method. Fault slip-rate data obtained from averaging geological and geodetic fault slip-rates is one of the necessary inputs for creating a PSHA model. Unfortunately, about 60% of faults in Indonesia do not have geological and/or geodetic fault slip-rate values. This research aims to obtain and analyze fault slip-rate values that have not been geologically and/or geodetically observed. The research is conducted by applying equations related to the earthquake-scaling relationship. The data used in this study is taken from the 2017 Indonesian Earthquake Source and Hazard Map (PuSGeN). From the data processing conducted, ranges of magnitude and fault slip-rates in Indonesia were obtained. The range of moment magnitude values of faults in Indonesia, respectively from PuSGeN data, calculations using Cheng et al.'s formula, and calculations using Gunawan's formula, are: 6.1 – 8.2; 5.8 – 8.2; and 6.3 – 8.0. Next, the range of fault slip-rate values in Indonesia, respectively from PuSGeN data, calculations using Cheng et al.'s formula, and calculations using Gunawan's formula, are: 0.05 – 35.00; 0.05 – 22.87; and 0.05 – 19.98. The differences between the three types of moment magnitudes are not very significant, with the highest difference being 1.4, whereas the differences between the three types of slip-rates are quite significant, with the highest difference being 34.92. The moment magnitude and slip-rate values calculated using Cheng et al.'s and Gunawan's methods show the highest level of similarity.